Leaders' Policies in Countering Radicalism at Leading Islamic Universities in East Java - Sulistyorini, Sulistyorini; Zuhriyah, Lailatuzz (IAIN Manado, 2025)
Article Leaders are the determinants of the security and comfort of the institutions they lead, this study aims to analyze and explore the policies of leaders in countering radicalism in Islamic universities which include policies for new students, students who are already studying and policies for Lecturers and Education Staff. This study uses a qualitative approach involving researchers as research instruments. In data collection, the rector is a key informant. Other informants are selected based on the snowball sampling technique. This process continues until the data is saturated. In addition to interviews, research data is collected through observation and written documents. The collected data is analyzed following the steps proposed by Miles and Huberman (1984), such as data reduction, data presentation, and drawing conclusions (illustration/verification). More specifically, data validation is carried out through triangulation. The results of the study show that the leader's policy for new students starts from students entering to fill out a google form created by the religious moderation house, in PBAK they are equipped with Islamic values that are rahmatan lilalamin and are required to reside in the ma'had and madin for one year, the policy for students who are already in college through the tridharma of higher education, namely learning that inserts religious moderation values, through KKN and research and the leader's policy for lecturers and education personnel by participating in religious moderation workshops, especially for young lecturers and new education staff.